2020
DOI: 10.1111/dme.14329
|View full text |Cite
|
Sign up to set email alerts
|

Oral antidiabetes agents for the management of inpatient hyperglycaemia: so far, yet so close

Abstract: Background Hyperglycaemia is an ongoing challenge in hospital settings and is associated with poor outcomes. Current recommendations for the management of inpatient hyperglycaemia suggest insulin as the main glucose-lowering treatment choice and limit the administration of oral antidiabetes agents to a small proportion of cases because of safety concerns. Aim To present and critically appraise the available evidence on the use of oral antidiabetes agents in the hospital setting and the risk-benefit balance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
11
0
3
Order By: Relevance
“…In such cases, the patient should be kept under close watch for hypoglycaemia, and an adjustment in insulin dose should be considered. The use of oral dipeptidyl peptidase-4 (DPP-4) inhibitors has also been reported to be a safe and effective treatment in patients with mild to moderate hyperglycaemia and in stable clinical condition, and a reduction of insulin dose may be needed in situations where these agents are co-administered with insulin [43]. The use or continuation of glucoselowering oral drugs other than DPP-4 inhibitors is generally not recommended for acutely ill patients with COVID-19 due to the potential for abrupt deterioration in clinical status [44].…”
Section: Concomitant Use Of Oral Agents With Potentialmentioning
confidence: 99%
“…In such cases, the patient should be kept under close watch for hypoglycaemia, and an adjustment in insulin dose should be considered. The use of oral dipeptidyl peptidase-4 (DPP-4) inhibitors has also been reported to be a safe and effective treatment in patients with mild to moderate hyperglycaemia and in stable clinical condition, and a reduction of insulin dose may be needed in situations where these agents are co-administered with insulin [43]. The use or continuation of glucoselowering oral drugs other than DPP-4 inhibitors is generally not recommended for acutely ill patients with COVID-19 due to the potential for abrupt deterioration in clinical status [44].…”
Section: Concomitant Use Of Oral Agents With Potentialmentioning
confidence: 99%
“…94 Side effects of the class mainly include negative effects on bone density, fluid retention, and cause of edema that might destabilize patients with heart and renal failure, whereas the CV safety of rosiglitazone has been debated. 95 Another class of oral glucose-lowering agents, dipeptidyl peptidase-4 (DPP-4) inhibitors, is known to exert immunomodulatory actions and has the potential to improve glycemic control and preserve β-cell mass in autoimmune diabetes. 78,79 Animal research has demonstrated that linagliptin prevents the autoimmune β-cell destruction and improves lumphocyte insulinitis in nonobese diabetic mice.…”
Section: Immunomodulatory Properties Of Glucoselowering Agentsmentioning
confidence: 99%
“…Specific agents within the class (saxagliptin and alogliptin), though, have been linked to an increased risk of hospitalization for HF. 95 In a post hoc analysis of the REWIND clinical program, treatment with the GLP-1 RA dulaglutide reduced HbA1c levels in positive GADA individuals. 100 Although the reduction was greater among those with low GADA titers, efficacy was also evident in GADA high patients.…”
Section: Immunomodulatory Properties Of Glucoselowering Agentsmentioning
confidence: 99%
See 2 more Smart Citations